Pengaruh Edukasi Keamanan Pangan terhadap Pengetahuan Pemilihan Jajanan pada Anak SD Kelas V di SDN 1 Landono Kabupaten Konawe Selatan - Stejiriawan, Nur Iknal; Ananda, Siti Hadrayanti; Abadi, Ellyani (Sekolah Tinggi Ilmu Kesehatan Karya Kesehatan, 2024)
Food is a basic need for every human being to be able to carry out physiological functions. Safe food is food that is free from microbes, chemicals and dangerous substances which, if intentionally or accidentally consumed by humans, will not cause health problems. School children are the forerunners of the nation's next generation. At this age, children have lots of busy activities, causing them to need a healthy physical condition. The aim of this research is to determine the effect of food safety education on knowledge of snack choices in class V children at SDN 1 Landono. The type of research used is pre-experimental design research. This research was conducted on one group, namely the experimental group that received treatment. The population in this study were all students from classes VA and VB, totaling 36 people, the sample was 33 people. Research results: Knowledge of snack selection among fifth grade elementary school children at SDN 1 Landono before being given education had an average score of 12.21. Knowledge of snack selection among fifth grade elementary school children at SDN 1 Landono after being given education had an average score of 13.39. There is an influence of food safety education on knowledge of snack choices in fifth grade elementary school students at SDN 1 Landono with p value = 0.000. Suggestion: For the SDN 1 Landono School, it is hoped that this research can provide input so that the school can continue to provide education about choosing healthy snacks for its students. For future researchers, it is hoped that this research can serve as input and reference material for future researchers.